Fear of Covid-19 and depression in psychology students from Ica - Chacaltana-Hernández, Katia Marilyn (2022)
The aim of this research is to establish the levels and the relationship that exists between fear of coronavirus and depression in psychology students from Ica. It is non-experimental, descriptive correlational, with the participation of 157 students from the Faculty of Psychology. of Ica, the following instruments were used: Scale of fear of coronavirus (Sars-cov2)-Peruvian version and Depressive Psychopathology Scale (EDP). The results found show 78. 4% of Fear of contracting Covid-19 and 20.4% have depressive symptoms, likewise, it was found that there is a direct and highly significant relationship between both study variables, no significant differences were found according to age and sex except for the academic cycle.